2016
DOI: 10.1007/s11936-016-0444-z
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Management in Intracranial Hemorrhage: Current Challenges and Opportunities

Abstract: Non-traumatic intracranial hemorrhage (i.e. intracerebral hemorrhage [ICH] and subarachnoid hemorrhage [SAH]) are more life threatening and least treatable despite being less common than ischemic stroke. Elevated blood pressure (BP) is a strong predictor of poor outcome in both ICH and SAH. Data from a landmark clinical trial INTERACT 2, wherein 2839 participants enrolled with spontaneous ICH were randomly assigned to receive intensive (target systolic BP <140 mmHg) or guideline recommended BP lowering therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…They likely reflect repeated episodes of blood leaking into the subarachnoid space from brittle and fragile CAA affected vessels. Siderosis is emerging as perhaps the most clinically relevant manifestation of the disease: (i) it is a trigger of transient focal neurological symptoms ('amyloid spells') (Greenberg et al, 1993;Charidimou et al, 2012b), expanding the CAA clinical imaging spectrum (Raposo et al, 2011;Calviere et al, 2016); (ii) it has been shown to carry a very high risk of future symptomatic lobar ICH (Linn et al, 2010;Charidimou et al, 2013c) with important implications for CAA clinical care, such as strict blood pressure control (Gorelick et al, 2011;Biffi et al, 2015;Hemphill et al, 2015;Carcel et al, 2016) and avoiding antithrombotics unless otherwise strongly indicated (Biffi et al, 2010;Charidimou et al, 2012a); and (iii) it may be an independent risk factor for new onset dementia after ICH (Moulin et al, 2016). Of note, siderosis exerts these effects independent of, and above any effect of coincident microbleeds (Greenberg et al, 2004;Biffi et al, 2010).…”
Section: Clinical Imaging Expression and Spectrum Of Cerebral Amyloidmentioning
confidence: 99%
“…They likely reflect repeated episodes of blood leaking into the subarachnoid space from brittle and fragile CAA affected vessels. Siderosis is emerging as perhaps the most clinically relevant manifestation of the disease: (i) it is a trigger of transient focal neurological symptoms ('amyloid spells') (Greenberg et al, 1993;Charidimou et al, 2012b), expanding the CAA clinical imaging spectrum (Raposo et al, 2011;Calviere et al, 2016); (ii) it has been shown to carry a very high risk of future symptomatic lobar ICH (Linn et al, 2010;Charidimou et al, 2013c) with important implications for CAA clinical care, such as strict blood pressure control (Gorelick et al, 2011;Biffi et al, 2015;Hemphill et al, 2015;Carcel et al, 2016) and avoiding antithrombotics unless otherwise strongly indicated (Biffi et al, 2010;Charidimou et al, 2012a); and (iii) it may be an independent risk factor for new onset dementia after ICH (Moulin et al, 2016). Of note, siderosis exerts these effects independent of, and above any effect of coincident microbleeds (Greenberg et al, 2004;Biffi et al, 2010).…”
Section: Clinical Imaging Expression and Spectrum Of Cerebral Amyloidmentioning
confidence: 99%
“…Despite the recommendation from the European Stroke Organization that SBP in SAH should be maintained below 180 mmHg in order to minimize the risk of rebleeding in managing ruptured aneurysms 19 , no optimal BP thresholds have yet been determined, given the absence of evidence from randomized clinical trials 20 . Moreover, there is also wide variability regarding BP management targeted on treatment of ruptured intracerebral aneurysms.…”
Section: Discussionmentioning
confidence: 99%